Electrical Characterization of Thin Films (TiO2: ZnO)1-x (GO)x / FTO Heterojunction Prepared by Spray Pyrolysis Technique. (July 2020) - Alsultani, M J; Abed, H H; Ghazi, R A; Mohammed, M A
Abstract: Thin films from (TiO2 : ZnO)1-x (GO)x (x=0.2, 0.4, 0.6, 0.8) ml have been prepared by spray pyrolysis technique through depositing on FTO coated glass substrates. Electrical is characteristic was investigated by current-voltage (I–V), capacitance-voltage (C–V) measurements. The (I-V) measurement showed that heterojunction from symmetric type (isotope), Ideality factor (β) value increased from1.63 to 2.48 where (β) > 1 the recombination current was dominates, rectification ratios increased from 30.62 to 77.43 because of reduction in the depletion layer from 127nm to 56.4nm which investigated by (C-V) measurements, as well as the built-in voltage (Vbi ) and the barrier height ØB decreased from 1.42 V to 0.65 V and 1.62 to 0.79eV respectively. The increase in graphene oxide ratio lead to increase in the majority carriers in turn leads to reduction in Fermi levels. Such tests showed that the electrical properties of the prepared thin films improved and indicated that GO acts as a semiconductor and can be used for flexible and transparent optical-electronic devices.